TINGKAT KESEGARAN JASMANI SISWA KELAS XI TEKNIK PEMESINAN SMKN 1 KARAWANG YANG AKAN MELAKSANAKAN PRAKTEK KERJA INDUSTRI - Moehamad Goeffan Rifai; Irfan Zinat Achmad; Rhama Nurwansyah Sumarsono (Jurnal Speed (Sport, Physical Education, Empowerment), 2021)
In the effort to establish the quality of human resources, physical education plays an important role in it. One aspect developed in physical education is physical fitness. This study aims to determine the level of physical fitness of students of class XI in engineering machineries SMKN 1 Karawang who will carry out industrial work practices. To answer the problem formulation that has been formulated, the authors use a descriptive approach with quantitative methods. Descriptive approach can be interpreted as research conducted to determine the value of independent variables, either one or more variables (independent) without making comparisons or connecting with other variables. It is a method to be able to find out the physical fitness level of students of class XI in machining techniques who will carry out industrial work practices at SMKN 1 Karawang. The design of this study is a survey research, while for sampling is 30 samples from a population of 107. Data collection techniques used to obtain data on physical fitness levels using TKJI tests aged 16-19. From the results of data analysis using quantitative descriptive analysis techniques with percentages, it can be concluded that the physical fitness level of class XI machining techniques that will carry out industrial work practices is in the category of "Medium" by 50%.